Thyroid symptom scoring index: an auxiliary guide to thyroid function tests: a prospective comparative study from a general hospital in South India - Hussain, Zahir S.; Rao, Smitha S.; Jabamalai, Ferdinant (International Surgery Journal, 2019)
Background: Thyroid disease has myriad manifestations. Thyroid stimulating hormone (TSH) and a paired determination of TSH and freeT4 would add to find out the degree of dysfunction with overutilization of thyroid function tests (TFT’s) as the symptoms are being overseen in the recent days. The objectives of the present study were to validate the clinical symptom scoring index for thyroid disorders using TSH and FT4. Methods: The clinical symptom scoring index consisting of 20 parameters was given to 110 patients presenting to our outpatient department with new onset thyroid-related complaints from June2018 to Spetemer2018. They were subjected to TFT (TSH and free T4) and classified accordingly. Statistical analysis was done and receiver operator curves (ROC) plotted. Results: The mean TSH for the 3 groups (hypothyroid, hyperthyroid and euthyroid) were 13.65, 0.31 and 1.7 mIu/ml respectively (normal value: NV-0.25-5). Mean FT4 were 0.58, 5.01 and 1.28 ng/dl respectively (normal value 0.82-1.51). Most frequent findings in biochemical hyperthyroidism were easy tremors (100%), tiredness (90%), palpitations (93%) and weight loss (75.6%). The clinical symptom scoring index had a sensitivity of 85% and accuracy rate of 86.76% with area under the curve (AUC) 0.865 on ROC analysis for the detection of hyperthyroidism. It had a 100% sensitivity and AUC 0.65 for hypothyroidism. Conclusions: The symptom scoring index for thyroid disorders was found to have good specificity, negative predictive value (NPV) and accuracy rate when correlated with TSH and FT4 for the detection of hyperthyroidism. In the developing countries, these score indices can aid as auxiliary diagnostic tools, reducing the load on referral centers.